Being excellent teams: managing innovative climate, politics, and team performance. (17th February 2020) - Lin, Chieh-Peng; Liu, Chu-Mei; Liu, Na-Ting; Huang, Hsu-Ting
Abstract : This research develops a team-level model based on transactive memory theory to analyze how teams achieve excellent performance by managing innovative climate and politics. In the model, team performance relates to innovative climate positively and politics negatively through the full mediation of transactive memory systems (TMS). Meanwhile, the effects of innovative climate and politics on TMS are moderated by perceived meaningfulness. Its empirical results reveal that team performance indirectly relates to innovative climate and politics via the full mediation of TMS. Besides, the positive relationship between innovative climate and TMS is moderated by perceived meaningfulness, such that the relationship is stronger when perceived meaningfulness is higher. Empirical testing of our model using the data collected from team personnel in Taiwan confirmed the applicability of the transactive memory theory among work teams. Last, managerial implications and research limitations are provided.